Public trust in manipulated elections: The role of election administration and media freedom. (December 2017) - Kerr, Nicholas; Lührmann, Anna
Abstract: As multiparty elections have become a global norm, scholars and policy experts regard public trust in elections as vital for regime legitimacy. However, very few cross-national studies have examined the consequences of electoral manipulation, including the manipulation of election administration and the media, on citizens' trust in elections. This paper addresses this gap by exploring how autonomy of election management bodies (EMBs) and media freedom individually and conjointly shape citizens' trust in elections. Citizens are more likely to express confidence in elections when EMBs display de-facto autonomy, and less likely to do so when mass media disseminate information independent of government control. Additionally, we suggest that EMB autonomy may not have a positive effect on public trust in elections if media freedom is low. Empirical findings based on recent survey data on public trust in 47 elections and expert data on de-facto EMB autonomy and media freedom support our hypotheses. Highlights: We explore how EMB autonomy and media freedom individually and conjointly shape citizens' trust in elections. We combine recent data from Afrobarometer and World Values Survey on public trust in elections in 47 elections. Citizens' trust in elections is positively associated with EMB autonomy and negatively associated with media freedom.